Application of the reaction class transition state theory to the kinetics of hydrogen abstraction reactions of alkanes by atomic chlorine - Tammarat Piansawan (2018)
Kinetics of the hydrogen abstraction reaction of the class alkane + Cl → alkyl + HCl was studied using reaction class transition state theory (RC-TST) combined with linear energy relationships (LERs). The thermal rate coefficients for the reference reaction of ethane + Cl → ethyl + HCl, calculated by the microcanonical variational transition state theory (μVT) incorporating small curvature tunneling (SCT), were taken from the literature. All necessary parameters were derived from density functional theory (DFT) calculations for a representative set of 29 reactions involving a range of hydrocarbons. Direct comparison to available experimental data reveals that the RC-TST/LER can predict rate coefficients for any reaction in the reaction class with acceptable accuracy. For the two test reactions outside of the representative set, our derived rate coefficients were in reasonable agreement with available data. Furthermore, our analyses indicate that RC-TST/LER gave systematic errors of less than 25% when compared to TST with one-dimensional Eckart tunneling approximation rate coefficients. © 2013 Elsevier B.V.